Clinical and radiological outcomes following surgical hip dislocation for paediatric hip pathologies, a prospective cohort study. Issue 3 (June 2023) - Ahern, Shane; O'Sullivan, Michael D.; Clesham, Kevin; Wade, Anna; Meleady, Elizabeth; Green, Connor
Abstract: Background: Surgical Hip Dislocation (SHD) is a powerful tool in the armamentarium of any surgeon treating conditions affecting the hips of children presenting with sequelae of a number of common conditions including Legg-CalvéPerthes disease (LCPD) and slipped capital femoral epiphysis (SCFE). Risks associated with the procedure are well described. We investigated to assess if SHD is associated with significant surgical risk and if it improved clinical outcomes for patients. Methods: We conducted a prospective cohort study. We reviewed 18 (11 males and 7 females; mean age 13.7 years (6–17) with symptomatic hip pathology, secondary to femoroacetabular impingement (FAI) between 2017 and 2021. All patients underwent a surgical hip dislocation approach and femoral head-neck osteochondroplasty, Head Split osteotomy or both. Clinical improvement was assessed using the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) index. The minimum follow-up was 6 months (mean, 22 months; range, 6–42 months). Results: WOMAC scores improved at final follow-up from 10 to 3 for pain, 33 to 10 for function, and 4 to 2 for the stiffness subscales. All radiographic measures improved significantly of the postoperative X-rays. No patients developed osteonecrosis, implant failure, deep infection, or nonunion. Conclusion: Surgical Hip Dislocation, in the short term, we found improvement in WOMAC scores and radiographic indices with a low complication rate. Highlights: The WOMAC scores show significant improvements during this follow up period. Radiographic parameters showed significant improvement across measured indices'. No radiographic evidence of avascular necrosis postsurgical hip dislocation.